Soil-transmitted helminthiasis: a critical but neglected factor influencing school participation of Aboriginal children in rural Malaysia - Ahmed, Abdulhamid; Al-Mekhlafi, Hesham Mahyoub; Azam, Mohammad Nurul; Ithoi, Init; Al-Adhroey, Abdulelah H.; Abdulsalam, Awatif Mohamed; Surin, Johari (Cambridge University Press, 2012)
Soil-transmitted helminthiasis (STH), among the most common neglected tropical diseases, is a major public health problem in Malaysia with a possible impact on the nutritional status and school participation of rural children. This study was carried out among Aboriginal schoolchildren, living in an endemic area for STH in Malaysia, to determine the possible relationship between intestinal helminthiasis and school absenteeism. We also evaluated whether successful treatment of the infection will affect school attendance among the subjects. Stool analysis revealed that more than 90 of the subjects were infected with at least 1 helminth species, with Ascaris lumbricoides and Trichuris trichiura infections being most prevalent. Infection of moderate-to-heavy worm burdens, low level of fathers' education and anaemia were identified as the significant predictors of high absenteeism among the subjects (P<0.05). Following treatment of the infected children, it was found that school absenteeism was reduced significantly (P<0.01). In conclusion, STH continues to have significant impacts on public health, particularly in rural communities with a negatively significant effect on the school participation of Aboriginal children. A school-based de-worming programme should be introduced and incorporated in the current educational assistance targeted towards the Aboriginal communities, under the auspices of the government.